2013
DOI: 10.5455/2319-2003.ijbcp20130826
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of antidiabetic drugs use in type-2 diabetic patients in a medicine outpatient clinic of a tertiary care teaching hospital

Abstract: Background: Diabetes mellitus (DM) is an important public health problem in developing countries. Drug utilisation study of antidiabetic agents is of paramount importance to promote rational drug use in diabetics and make available valuable information for the healthcare team. The aim of study was to investigate the drug utilization pattern in type-2 diabetic patients. Methods: A prospective, cross-sectional study was carried out in medicine outpatient clinic of tertiary care hospital, Ahmedabad for eight week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
33
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 15 publications
(16 reference statements)
14
33
3
Order By: Relevance
“…17,18 However, the results are in contrast to a few studies conducted in India and other countries which have reported either male or female preponderance. [19][20][21][22][23] Majority of our patients were in the age group of 51-60 years (40%) which is in concordance with the earlier published literature. 17,19,21,24 The mean age of the patients in the present study was 57.6 years (age range: 18-79 years) which is similar to that obtained in studies conducted in Nepal and Ahmedabad in which the mean age of patients was 56.9 and 56.8 years respectively.…”
Section: Discussionsupporting
confidence: 80%
“…17,18 However, the results are in contrast to a few studies conducted in India and other countries which have reported either male or female preponderance. [19][20][21][22][23] Majority of our patients were in the age group of 51-60 years (40%) which is in concordance with the earlier published literature. 17,19,21,24 The mean age of the patients in the present study was 57.6 years (age range: 18-79 years) which is similar to that obtained in studies conducted in Nepal and Ahmedabad in which the mean age of patients was 56.9 and 56.8 years respectively.…”
Section: Discussionsupporting
confidence: 80%
“…Different studies also reported similar observation with regard to the co-morbidity in patients with diabetes. 8,11,[16][17][18] The average number of drugs per prescription was 3.04 which is comparable to the study from UAE. 8 Prescriptions with 5 and more than 5 drugs were found among patients above 50 years of age and with co-morbidities.…”
Section: Discussionsupporting
confidence: 66%
“…7,11,15,16,[18][19][20] Among the sulfonylureas, glimepiride was the most commonly prescribed drug along with metformin which is similar to studies. 10,18 Metformin is one of the safest and most cost effective drug compared to other drugs in terms of hypoglycaemia and decreasing BMI, hence this could be the most probable reason for this finding. Also this finding is in accordance with the clinical guidelines given by Canadian Diabetes Association, International Diabetes Federation, and National Institute of Health and Clinical Excellence.…”
Section: Discussionsupporting
confidence: 51%
“…13 Another study published that there was optimal adherence to guidelines in Sweden in home health care settings than residents at nursing homes. 14,15 This study found there was optimal adherence to AACE/ ACE guidelines in our institution resulting in better patient care. In dual therapy, triple and Insulin therapy there was unprecedented adherence.…”
Section: Discussionmentioning
confidence: 99%